ANALISIS PENGGUNAAN MOBILE JAMINAN KESEHATAN NASIONAL DENGAN MENGGUNAKAN METODE TECHNOLOGY ACCEPTANCE MODEL (TAM) DI RUMAH SAKIT ISLAM METRO - Retno Sofy Safira; Windi Pertiwi; Yogi Catur Putra; Maya Aprilianingsih (Journal of Hospital Administration and Management (JHAM), 2026)
Digital transformation through the Mobile JKN app aims to improve healthcare services, yet getting patients to actually use it remains a challenge. This study uses the Technology Acceptance Model (TAM) to analyze how perceived usefulness, ease of use, and user attitude influence the intention to use the app at Islam Metro Hospital. The research design used in this study is quantitative with a cross-sectional approach. The population consisted of 1,809 Mobile JKN users at Islam Metro Hospital, from which a sample of 328 respondents was selected using a purposive sampling technique. Data were collected via questionnaires distributed to these 328 respondents, followed by validity and reliability tests, and correlation analysis using the Spearman rank test. The research findings indicate a significance value of 0.000 (which is leq 0.05), meaning there is a significant relationship between the three variables perceived usefulness, perceived ease of use, and attitude toward use and the Behavioral Intention to Use the Mobile JKN application at Islam Metro Hospital, leading to the rejection of H0. The correlation coefficients for Perceived Usefulness (r = 0.523) and Perceived Ease of Use (r = 0.551) fall into the moderate category, while attitude toward use (r = 0.723) shows a strong relationship and stands as the most dominant factor. Participants' intention to use the Mobile JKN application is heavily determined by a positive attitude, which is formed by the benefits and ease of use perceived by the users. For future research, it is recommended to include other variables outside the TAM model, such as internet connection quality or facility support factors, considering that there are still influencing factors beyond the variables examined in this study.